Application of AGPU for Matrix Converters - Nithin T Abraham; C.A Pradeep Kumar; Shaema Lizbeth Mathew (Institute of Advanced Engineering and Science, 2014)
A simple PI control loop for the matrix converter system is designed in the simulation to maintain a constant output voltage inspite of any disturbance in the source. The single phase matrix converter employs a modified safe-commutation strategy, which results in the elimination of voltage spikes on switches, without the need of a snubber circuit when there is an inductive load being utilized. This is facilitated through the proper switching control algorithm. The sine PWM pulses are generated as switching pulses to the converter to reduce the THD.DOI: http://dx.doi.org/10.11591/ijpeds.v5i1.5340